2021
DOI: 10.1002/ajb2.1786
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory and jasmonate treatment affect reproductive traits in wild Lima bean, but without transgenerational effects

Abstract: Premise: Plant responses to herbivores and their elicitors include changes in traits associated with phenology, defense, and reproduction. Induced responses by chewing herbivores are known to be hormonally mediated by the jasmonate pathway and can cascade and affect late-season seed predators and pollinators. Moreover, herbivoreinduced plant responses can be transmitted to the next generation. Whether herbivore-induced transgenerational effects also apply to phenological traits is less well understood. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…To our knowledge, effects of herbivory on flowering time and flower production have been documented but are still scarce (Brys et al, 2011; Paige & Whitham, 1987; Strauss et al, 2001). Earlier studies have reported variable effects across species with some showing acceleration of flowering upon feeding (Bustos‐Segura et al, 2021), while others have shown a delay to flowering (Agrawal et al, 1999; Lemoine et al, 2017) or a reduction in the number of flowers produced (Strauss et al, 2001). This variation could depend on the amount of leaf damage caused by herbivory as plants may compensate for low leaf herbivory by producing a greater number of flowers and seeds (Poveda et al, 2013; Poveda et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, effects of herbivory on flowering time and flower production have been documented but are still scarce (Brys et al, 2011; Paige & Whitham, 1987; Strauss et al, 2001). Earlier studies have reported variable effects across species with some showing acceleration of flowering upon feeding (Bustos‐Segura et al, 2021), while others have shown a delay to flowering (Agrawal et al, 1999; Lemoine et al, 2017) or a reduction in the number of flowers produced (Strauss et al, 2001). This variation could depend on the amount of leaf damage caused by herbivory as plants may compensate for low leaf herbivory by producing a greater number of flowers and seeds (Poveda et al, 2013; Poveda et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hu et al (2021) demonstrated that MYCs repress cell proliferation in the seed integument. Studies showing that elicitation of leaf defence via exogenous JA compromises reproductive performance (Baldwin, 1998;Agrawal et al, 1999;Redman et al, 2001;Bustos-Segura et al, 2021) have suggested that the redirection of nutrients to the biosynthesis of defence compounds may contribute to declines in reproductive fitness. For example, JA-elicited defence reduced the availability of N for use in seed production (Baldwin et al, 1998).…”
Section: Myc Tfs Exert Negative Pleiotropic Effects On Reproductive P...mentioning
confidence: 99%
“…The ability of exogenous JA to compromise reproductive output supports the notion that induction of plant defence carries fitness costs (Baldwin, 1998; Baldwin et al ., 1998; Agrawal et al ., 1999; Redman et al ., 2001; Bustos‐Segura et al ., 2021). These observations are consistent with genetic evidence showing that the mutation of 10 JAZ s in Arabidopsis, or loss of the single JAZ gene in the liverwort Marchantia polymorpha , compromises reproductive success (Guo et al ., 2018b; Howe & Yoshida, 2019; Monte et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%